A Case Study Regarding Vibration-Induced Texturing in Turning - Talia Cristina da Silva Gibim; Felipe Bertolotti Savella; Renato Trevilato; Sidney Bruce Shiki; Carlos E.H. Ventura; Armando Ítalo Sette Antonialli (Materials Research)
This paper presents a case study regarding the hard turning of tool steel specimens when some insidious surface patterns were observed beyond the usual parallel feed marks. An optical three-dimensional measuring device was used to characterize and compare common reference surfaces and textured profiles. Subsequently, these data were analyzed using an image processing computational tool, through which it was possible to infer that, indeed, the surface with an unusual appearance exhibited a very well-defined orientation texture. The vibration monitoring data during the turning process of the samples were then compared through spectral density analysis of the signal, from which a dominant frequency was observed in the range of 3100 to 3300 Hz for both, but with a considerably higher amplitude peak for the textured one, indicating an unstable cut, i.e., one subjected to excessive vibrations. Finally, the experimental modal analysis performed on the tool used identified a fundamental frequency of the same order of magnitude, which allows for establishing a potentially causal correlation between the occurrence of chatter and the obtaining of the textured surface. This technique may be a pleasant opportunity to improve the tribology performance of tools, as the potential of textures are well presented in recent studies.